The Effect of Job Satisfaction and Work Motivation on Employee Performance in Pekanbaru City Sub-District in Pekanbaru City - Imam Hanafi; Iyoyo Sudianto; Hamsal Hamsal; Hidayat Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: The population in this research is all employees who work at the District Office and the sampling technique uses census sampling, namely all employees are used as a research sample, totaling 36 people. Methodology/approach: This research aims to analyze the influence of job satisfaction and work motivation on employee performance in Pekanbaru City District in Pekanbaru City. Results/findings: The results of this research show that job satisfaction and work motivation partially and simultaneously have a significant positive effect on employee performance in Pekanbaru City District in Pekanbaru City. Conclusions: Job satisfaction and work motivation significantly and positively influence employee performance, explaining 64.1% of its variation. Improving bonuses, recognition, and teamwork can further enhance performance. Limitations: This research aims to analyze the influence of job satisfaction and work motivation on employee performance in Pekanbaru City District in Pekanbaru City. Contribution: Provides evidence and practical guidance for improving public sector performance through better incentives and motivation strategies.